A Natural History of the Purple Swamphen (Porphyrio porphyrio) - Elise V. Pearlstine; Juan Sebastian Ortiz (EDIS, 2010)
WEC272, a 6-page illustrated fact sheet by Elise V. Pearlstine and Juan Sebastian Ortiz, describes this non-native gallinaceous bird from the Indian subcontinent — background, description, similar species, habits, habitat, food, nesting and reproduction, potential ecological impacts, and legal aspects. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, December 2009.